Handbook of Trace Analysis Fundamentals and Applications - Baranowska, Irena; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This handbook is unique in its comprehensive coverage of the subject and focus on practical applications in diverse fields. It includes methods for sample preparation, the role of certified reference materials, calibration methods and statistical evaluation of the results. Problems concerning inorganic and bioinorganic speciation analysis, as well as special aspects such as trace analysis of noble metals, radionuclides, and volatile organic compounds are also discussed. A significant part of the content presents applications of methods and procedures in medicine (metabolomics and therapeutic drug monitoring); pharmacy (the analysis of contaminants in drugs); studies of environmental samples; food samples and forensic analytics - essential examples that will also facilitate problem solving in related areas.
Part I General issues -- Characteristic and specificity of trace analysis -- Quality evaluation of analytical results - errors classification, uncertainty estimation -- Part II Application -- Trace analysis of selected organic compounds -- Analysis of drugs impurities -- Part III Special aspects -- Inorganic and bioinorganic speciation analysis - selected problems.
Keywords: Analytical chemistry; Pharmaceutical chemistry; Environmental monitoring; Medicine -- Research; Biology -- Research; Forensic sciences; Food science; Analytical Chemistry; Pharmaceutics; Environmental Monitoring; Biomedical Research; Forensic Science; Food Science